ATP-Independent Chaperones - Mitra, Rishav; Wu, Kevin; Lee, Changhan; Bardwell, James C.A. (Annual Review of Biophysics, 2022)
The folding of proteins into their native structure is crucial for the functioning of all biological processes. Molecular chaperones are guardians of the proteome that assist in protein folding and prevent the accumulation of aberrant protein conformations that can lead to proteotoxicity. ATP-independent chaperones do not require ATP to regulate their functional cycle. Although these chaperones have been traditionally regarded as passive holdases that merely prevent aggregation, recent work has shown that they can directly affect the folding energy landscape by tuning their affinity to various folding states of the client. This review focuses on emerging paradigms in the mechanism of action of ATP-independent chaperones and on the various modes of regulating client binding and release.
Keywords: Adenosine Triphosphate; Humans; Molecular Chaperones; Protein Conformation; Protein Folding; holdase; protein folding; small heat shock proteins; Spy; SurA; trigger factor